2020
DOI: 10.3390/ijms21228618
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Intra-Articular Microbiome in the Osteoarthritic Knee

Abstract: Osteoarthritis (OA) is the most common joint disorder in the United States, and the gut microbiome has recently emerged as a potential etiologic factor in OA development. Recent studies have shown that a microbiome is present at joint synovia. Therefore, we aimed to characterize the intra-articular microbiome within osteoarthritic synovia and to illustrate its role in OA disease progression. RNA-sequencing data from OA patient synovial tissue was aligned to a library of microbial reference genomes to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Of the 43 differentially abundant microbes, 27 of them were species of Pseudomonas . The bacterium found in OA synovial biopsies can be linked to immune signatures and immune cell types ( Tsai et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 43 differentially abundant microbes, 27 of them were species of Pseudomonas . The bacterium found in OA synovial biopsies can be linked to immune signatures and immune cell types ( Tsai et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 8 overlapping DEGs that were found have a pivotal role in modulating inflammation and degradation of cartilage, and more so the inflammatory pathway was discussed to be differently expressed in all 5 articles chosen for this review. Interestingly, the differentially abundant bacteria found by Tsai et al were majority from the species Pseudomonas ( Tsai et al, 2020 ). There were also E. Coli differentially expressed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown that bacteria or related compounds (i.e., LPS and peptidoglycan) cross the intestinal barrier and enter the systemic circulation to mediate OA ( Lorenzo et al., 2019 ). Based on the simultaneous assessment of the microbiome in the gut, blood and joints, Tsai et al. (2020) also made the hypothesis that a “leaky” gut allows microbiota, associated with dysregulation of immune gene signaling and promoting inflammation, to migrate from the gut to the joints, leading to the onset of OA.…”
Section: Gut Microbiota Is Involved In the Development Of Oa Through ...mentioning
confidence: 99%
“…It has been stated that old age may be associated with intestinal dysbiosis and increased gut permeability, which could promote a “leakage” of gut microbes into tissues, thus leading to a chronic proinflammatory state [ 173 , 174 ]. Tsai et al aimed to characterize the immunological signature of the microbiome in osteoarthritic knee synovium, finding marked discrepancy in microbial abundance in patients compared to healthy controls [ 175 ]. Whereas intestinal dysbiosis has been linked to synovial inflammation in knee OA, the impact of probiotic use on disease progression have not been studied extensively in clinical trials [ 176 , 177 ].…”
Section: Therapeutic Approach To Synovial Inflammation In Knee Ostmentioning
confidence: 99%